Prognosis and therapy for ruptured hepatocellular carcinoma: Problems with staging and treatment strategy. Issue 3 (March 2015) - Hiraoka, Atsushi; Kawamura, Tomoe; Aibiki, Toshihiko; Okudaira, Tomonari; Toshimori, Akiko; Yamago, Hiroka; Nakahara, Hiromasa; Suga, Yoshifumi; Azemoto, Nobuaki; Miyata, Hideki; Miyamoto, Yasunao; Ninomiya, Tomoyuki; et al.
Highlights: Although a patient with a ruptured HCC is generally considered to have a poor prognosis and treated as T4 in the 7th edition of the AJCC/UICC, some ruptured cases show a good clinical course. There are no clear criteria established for treating a ruptured hepatocellular carcinoma (HCC) which is classified as T4 in TNM stage of UICC 7th. This article describes that better prognosis can be expected with curative treatment in patients with a ruptured HCC, especially those with a single tumor, and without decompensated liver cirrhosis and PVTT/extrahepatic metastasis. T4 classification should not include all types of ruptured HCC. Abstract: Background: There are no clear criteria established for treating a ruptured hepatocellular carcinoma (HCC). To elucidate the clinical features of affected patients, we examined prognosis and therapy choices. Materials/methods: We enrolled 67 patients treated for a ruptured HCC (HCV 44, HBV 5, HBV + HCV 1, alcohol 2, others 15; naïve HCC 34, recurrent 33) from 2000 to 2013, and investigated their clinical background and prognosis. Results: Median survival time (MST) for all cases was 4 months. For patients who survived for more than 1 year after rupture, the percentages of Child-Pugh C and positive for portal vein tumor thrombosis (PVTT)/extrahepatic metastasis were less than for those who died within 1 year. Child-Pugh classification (A:B:C = 14:15:5 vs. 4:9:20, P < 0.001) was better, while the percentage of patients with multiple tumors was lower [19/34 (55.9%) vs. 29/33 (87.9%), respectively; P < 0.001] in the naïve group. The 1- and 3-year survival rates were better in the naïve as compared to the recurrent group (60.6% and 33.3% vs. 12.6% and 0%, respectively; P < 0.01). MST according to modified TNM stage (UICC 7th) calculated after exclusion of T4 factor of rupture, stage I was better than others (22.7 vs. (II) 2.2, (III) 1.2, and (IV) 0.7 months) ( P = 0.010). Conclusion: In patients with a ruptured HCC, especially those with a single tumor, and without decompensated liver cirrhosis and PVTT/extrahepatic metastasis, better prognosis can be expected with curative treatment. The present naïve group included more of such cases than the recurrent group, indicating the effectiveness of curative therapy.